2017
DOI: 10.1038/tp.2017.62
|View full text |Cite
|
Sign up to set email alerts
|

Childhood life events, immune activation and the development of mood and anxiety disorders: the TRAILS study

Abstract: The experience of childhood life events is associated with higher vulnerability to develop psychiatric disorders. One of the pathways suggested to lead to this vulnerability is activation of the immune system. The aim of this study is to find out whether the association between childhood life events and the development of mood and anxiety disorders is predicted by the activation of the immune system. This study was performed in TRAILS, a large prospective population cohort, from which a subgroup was selected (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 69 publications
(101 reference statements)
0
24
0
Order By: Relevance
“…Being newly widowed was related to depressive symptoms, whereas being newly divorced increased the risk of poor social support. There is also longitudinal evidence for life events related to the development of anxiety disorders (Jonker et al 2017). With reference to morbidity years, increased failure of successful aging was observed, especially after medical illness such as stroke (Kornerup et al 2010), respiratory system disease (Lietzén et al 2011), cancer (Lillberg et al 2003), diabetes and visceral adiposity (Mooy et al 2000).…”
Section: Relationship Of Life Events With Health-related Variablesmentioning
confidence: 99%
“…Being newly widowed was related to depressive symptoms, whereas being newly divorced increased the risk of poor social support. There is also longitudinal evidence for life events related to the development of anxiety disorders (Jonker et al 2017). With reference to morbidity years, increased failure of successful aging was observed, especially after medical illness such as stroke (Kornerup et al 2010), respiratory system disease (Lietzén et al 2011), cancer (Lillberg et al 2003), diabetes and visceral adiposity (Mooy et al 2000).…”
Section: Relationship Of Life Events With Health-related Variablesmentioning
confidence: 99%
“…Interestingly, in one study, CMV seropositivity influenced mood disorders differentially among males and females, associating with carrying a lower risk of mood disorders in males [13]. Also, the association between mental health and HSV-1 and EBV [10,11,[13][14][15][16][17][18][19][20][21] has been studied, with somewhat conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…In the aforementioned study, previous anxiety disorder was associated with increased levels of IL‐6 in the follow‐up evaluation . However, a study on childhood life events, immune activation and the development of mood and anxiety disorders indicated that inflammatory markers were not associated with the development of anxiety disorders or mood disorders . Therefore, inflammation may not fully explain the association between NO levels and anxiety.…”
Section: Discussionmentioning
confidence: 99%